Ligand-modulated folding of the full-length adenine riboswitch probed by NMR and single-molecule FRET spectroscopy - Warhaut, Sven; Heilemann, Mike (Nucleic acids symposium series, 2017)
The full-length translation-regulating add adenine riboswitch (Asw) from Vibrio vulnificus has a more complex conformational space than its isolated aptamer domain. In addition to the predicted apo (apoA) and holo conformation that feature the conserved three-way junctional purine riboswitch aptamer, it adopts a second apo (apoB) conformation with a fundamentally different secondary structure. Here, we characterized the ligand-dependent conformational dynamics of the full-length add Asw by NMR and by single-molecule FRET (smFRET) spectroscopy. Both methods revealed an adenine-induced secondary structure switch from the apoB-form to the apoA-form that involves no tertiary structural interactions between aptamer and expression platform. This strongly suggests that the add Asw triggers translation by capturing the apoA-form secondary structure in the holo state. Intriguingly, NMR indicated a homogenous, docked aptamer kissing loop fold for apoA and holo, while smFRET showed persistent aptamer kissing loop docking dynamics between comparably stable, undocked and docked substates of the apoA and the holo conformation. Unraveling the folding of large junctional riboswitches thus requires the integration of complementary solution structural techniques such as NMR and smFRET.